2009
DOI: 10.1111/j.1440-1843.2009.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng saponins attenuate acute lung injury induced by intestinal ischaemia/reperfusion in rats

Abstract: Administration of PNS before reperfusion injury alleviates acute lung injury induced by II/R, and this is attributable to the antioxidant and anti-inflammatory effects of PNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In a previous study, we showed that PNS administration decreased bacterial translocation and reduced pulmonary parenchymal damage, following II/R in rats. Furthermore, PNS was observed to reduce the activity of oxidative enzymes, the levels of MDA and nitric oxide, the activity of inducible nitric oxide synthase in the lung tissue and the levels of pro-inflammatory cytokines in the plasma (22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we showed that PNS administration decreased bacterial translocation and reduced pulmonary parenchymal damage, following II/R in rats. Furthermore, PNS was observed to reduce the activity of oxidative enzymes, the levels of MDA and nitric oxide, the activity of inducible nitric oxide synthase in the lung tissue and the levels of pro-inflammatory cytokines in the plasma (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical investigations have revealed a positive correlation between mortality and levels of circulating TNF-α, IL-1β, IL-6 and IL-8 in ALI (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In the present study, the reduction in inflammatory cytokine levels observed in the plasma of ALI rats following PNS treatment may have contributed to a reduction in leukocyte adhesion and infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PNS dose (100 mg/kg) in vivo was selected based on the previous studies (Rong et al, 2009;Yang et al, 2010;Zhang et al, 2008) with 100 mg/kg iv. in rats, 200 mg/kg ip.…”
Section: Animalsmentioning
confidence: 99%